The Effect of the TAR Technique (Dive, Observe, Arrange) on the Descriptive Writing Ability of Grade XI Students at SMK Willem Iskander - Hafis, Abdul; Payana, Wita Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of the TAR technique (Dive, Observe, Arrange) on the descriptive writing skills of eleventh-grade students at SMK Willem Iskander. Although the curriculum for vocational high schools requires students at this level to be able to produce descriptive texts, their writing proficiency remains below the expected standard. One contributing factor is the use of conventional teaching strategies that do not stimulate students’ creativity or active involvement in the learning process. The TAR technique, grounded in contextual learning principles, encourages an active, meaningful, and engaging learning environment by positioning students as the main actors in the classroom. The study employed an experimental method using a one-group pretest–posttest design. The research population consisted of 128 students across four classes, and a total of 32 students were selected as the sample. The findings revealed that prior to the implementation of the TAR technique, students’ descriptive writing ability was categorized as fair, with a mean score of 69.12. After the intervention, students’ performance improved to the good category with a mean score of 76.75. Statistical analysis produced a two-tailed significance value of 0.002, which is lower than the threshold of α = 0.05, indicating a significant difference between the pretest and posttest scores. Thus, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, confirming that the TAR technique has a significant effect on students’ ability to write descriptive texts.